Analisis pemetaan media tentang pembiayaan rahn di Indonesia dengan NVivo : Studi literatur review - Bagaskara, Doni Yusuf; Rohmadi, Rohmadi (Nur Science Institute, 2024)
This research aims to determine a media mapping analysis of Rahn Financing in Indonesia using the NVivo tool. This research uses qualitative methodology assisted by NVivo and a literature review. Several data analysis techniques in this research include firstly mapping the number of news article codes based on qualitative analysis such as meaning, objectives, terms and conditions, and laws, regarding